UJI BEBERAPA KONSENTRASI EKSTRAK TEPUNG DAUN SIRSAK (Annona muricata L.)MENGENDALIKAN LARVA Oryctes rhinoceros L. - Irwanto Irwanto; Hafiz Fauzanah Fauzanah; Desita Salbiah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
This research aims to obtain a concentration of soursop leaf flour extract which is effective to control the larvae of Oryctes rhinoceros L. The research was conducted at the Plant Pest Laboratory, Faculty of Agriculture, Riau University. The research was conducted for two months from April 2019 to May 2019. The research was conducted experimentally using a completely randomized design (CRD) consisting of 5 treatments and 4 replications, so that 20 experimental units were obtained. The treatments given were the concentration of soursop leaf extract 0 g.l-1 water, 25 gl-1 water, 50 gl-1 water, 75 gl-1 water and 100 gl-1 water. The parameters observed were the initial time of death, lethal time, lethal concentration, daily mortality, total mortality, temperature and humidity. The observed parameters data were analyzed by variance and followed by LSD at 5% level. The results showed that giving of soursop leaf powder extract at the higest concentration is 100 g.l-1 water was control O. rhinoceros L. larvae with a total mortality of 60%. This has not been effective in controlling O. rhinoceros L. larvae because it has not been able to cause a total mortality above 80%. The correct concentration caused a total mortality of 50% of O. rhinoceros L. larvae was 8.4% or the equivalent of 84 g.l-1 water extract of soursop leaf flour. The concentration that was able to produce a total mortality of 95% of O. rhinoceros L. larvae was 55.2% or the equivalent of 552 g.l-1 water extract of soursop leaf flour. Keywords:Oryctes rhinoceros, extract of soursop leaf flour, concentration, botanical insecticide